Effect of rotavirus vaccination offer to children observed in Italy between 2010-2018. (13th November 2019) - Antinolfi, F; Brunelli, L; Gallo, T; Valent, F
Abstract: Background: Rotavirus (RV) is the most common cause of gastroenteritis (GE) among children under 5 years. Since 2012 Friuli Venezia Giulia (FVG) Region (Italy) has offered free RV vaccination to low birthweight preterm and other at-risk babies. Starting from 2018, the offer has been extended to all newborns. Aim of the study is to investigate the effectiveness of RV vaccination offer on coverage and GE-related hospital admissions among FVG children under 1 year between 2010-2018. Methods: With a retrospective analysis we identified FVG Region children <1y with at least one dose of RV vaccine and children <1y admitted to hospital with a diagnosis of Non-Specific GE (NSGE; ICD9-CM codes 001-009) and RVGE (008.61) from 2010 to 2018. Vaccination coverage and hospitalization risk in each annual child cohort were calculated. Hospitalization and vaccination data were also linked using a univocal anonymous stochastic key. Results: Of 77, 330 children (51% males) born in FVG during 2010-2018, 8209 (11%) were vaccinated for RV. Coverage progressively increased from 0.2% in 2010 (22/9736) to 23% in 2017 (1782/7747) and then almost tripled in 2018 reaching 67% (5006/7425). During the 9 years observed, 414 children were hospitalized for NSGE (0.5%) and 172 for RVGE (0.2%). NSGE hospitalizations started from 48 (0.5%) in 2010 and reached 58 (0.8%) in 2018. Admissions for RVGE were 27 (0.3%) in 2010 and decreased to 15 (0.2%) in 2018. Annual hospitalization rate fluctuated with no clear pattern. In the observation period, 11 RV vaccinated children were admitted to hospital for NSGE (2.6% of total NSGE admissions), 1 of them specifically with RVGE. Conclusions: The offer of RV vaccination to newborns results to be effective to gain vaccine coverage among children under 5 years. The impact of this offer on GE-related hospital admission and RVGE in particular cannot be properly evaluated yet, as not enough time has passed since the implementation of free offer to all newborns. Key messages: Defining and implementing an appropriate vaccination offer is essential to ensure adequate levels of coverage against Rotavirus among children under 5 years. The evaluation of the effect of Rotavirus vaccination on hospital admissions for NSGE and RVGE needs a careful and continuous assessment in next years.